DISKRIMINASI PELAYANAN MASYARAKAT DI KANTOR KECAMATAN PADANG UTARA KOTA PADANG - , JUNIE NURSYAMZA, Dr. Ely Susanto,MBA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As a leading line of community service, the district needs to restructure the service which often discriminatory. The North District is a district locates in the center of the padang city with a heterogeneous population. Discrimination of service that occurs is also recognized by the Secretary of the city of Padang in a meeting with Padang City PNS. The purpose of this research is to know the forms and causes of discrimination at community service in the office of padang utara padang city.This research using a method of positivistic with a qualitative approach. The data collected is the primary data and secondary data. Primary data were obtained directly from respondents, while secondaru data obtained for do not go directly from documents that are relevant to the theme of research. The data collection technique were through the study of librarianship and field studies through interviews, observation and documentation. Collected data were analyzed by positivistic qualitative technique. Discrimination in community service is an act of service differentiation against a person or group of people whether time and the cost of service attitude is shown, as well as the procedure are given. The behavior of corrupt officials, abuse of authority and lack of skill led to the establishment of the service can not be professional in serving communities giving rise to discrimination. The influence of local culture, a hierarchical culture in the bureaucracy culture also created a culture service inclined to the officials and rulers. So are the low income and absence of appreciation for good performance, has made the services officers to serve because of money. This research result indicates there were discrimination treatmen done by the services apparatus of padang utara district by distinguishing the time and cost of service, attitude of officers as well as procedures that set out to the common community with a certain group of people. The difference is done mainly on among the rich, officials, community leaders and political figures. Not found any discrimination due to the factors of race and reliogion. This happens due to the large number of bureaucratic pathology contained in the organization of padang utara district. Then the service culture still affected by the paternalistic culture and local culture as well as service culture which has been hereditary within the systemâs of districts service in Indonesia. Social motives and economic motives also became the cause of yhe occurrence of discrimination in the service of padang utara district. The rank and the potition of a person both in Government and in the society as well as the relationship with proximity of apparatus highly influential to the service. So also with the low income services officers and not strictly speaking enforcement of reward and punishment leads to poor quality of service. Determination of required procedures of service with minimum standard. Service which usually 3 days became one hour. So that all people can be catered for with the treatment, procedure and the same time, and when there is a deviation can be reported and acted upon immediately.